Technologies and Materials for Carbon Dioxide Capture - Susanti, Indri (Science Education and Application Journal, 2019)
This paper was aims to review the technologies and materials for CO2 capture. Carbon dioxide is one of the triggers for the greenhouse effect and global warming. Some methods to reduce CO2 are separation technologies include air capture, CO2 Capture Utilization and Storage (CCUS) and CO2 Capture and Storage (CCS) technology. CCS technology have several systems namely post-combution, pre-combustion and oxy-fuel combustion. Post-combution systems can be done in various systems including absorption, adsorption, membrane, and cryogenic. Adsorption proses for CO2 capture applied with porous material such us mesopore silica, zeolite, carbon, MOF dan COF. This review was described the advantages and disadvantages of each technology for CO2 capture. Materials for CO2 adsorption also descibed in this review.